Diel patterning in the bacterial community associated with the sea anemone Nematostella vectensis. Issue 17 (13th August 2019) - Leach, Whitney B.; Carrier, Tyler J.; Reitzel, Adam M.
Abstract: Microbes can play an important role in the physiology of animals by providing essential nutrients, inducing immune pathways, and influencing the specific species that compose the microbiome through competitive or facilitatory interactions. The community of microbes associated with animals can be dynamic depending on the local environment, and factors that influence the composition of the microbiome are essential to our understanding of how microbes may influence the biology of their animal hosts. Regularly repeated changes in the environment, such as diel lighting, can result in two different organismal responses: a direct response to the presence and absence of exogenous light and endogenous rhythms resulting from a molecular circadian clock, both of which can influence the associated microbiota. Here, we report how diel lighting and a potential circadian clock impacts the diversity and relative abundance of bacteria in the model cnidarian Nematostella vectensis using an amplicon‐based sequencing approach. Comparisons of bacterial communities associated with anemones cultured in constant darkness and in light:dark conditions revealed that individuals entrained in the dark had a more diverse microbiota. Overall community composition showed little variation over a 24‐hr period in either treatment; however, abundances of individual bacterial OTUs showed significant cycling in each treatment. A comparative analysis of genes involved in the innate immune system of cnidarians showed differential expression between lighting conditions in N. vectensis, with significant up‐regulation during long‐term darkness for a subset of genes. Together, our studies support a hypothesis that the bacterial community associated with this species is relatively stable under diel light conditions when compared with static conditions and that particular bacterial members may have time‐dependent abundance that coincides with the diel photoperiod in an otherwise stable community. Abstract : Host‐associated microbial communities play a fundamental role in many components of animal biology. These communities are dynamic and exhibit shifts in composition based on the local environment. Regular, repeated shifts in the environment (e.g., solar light cycles) may be one such factor, whereby exogenous light cues endogenous rhythms that lead to patterns among these communities. Here, we report how diel light and a potential circadian clock impacts the diversity and relative abundance of bacteria in a model cnidarian using a sequence‐based and comparative approach.